MODEL WISATA BUDAYA BERBASIS CERITA PANJI (CULTURE TOURISM MODEL BASED ON PANJI STORIES) - Satrya, I Dewa Gde; Indrianto, Agoes Tinus Lis (Balai Pelestarian Kebudayaan Wilayah X, 2017)
Cerita Panji berkisah mengenai Kerajaan Kadiri, berkembang pesat pada masa Majapahit. Ragam ekspresi Budaya Panji dalam bentuk sastra oral, sastra visual, seni pertunjukan dan nilai-nilai kehidupan. Artikel ini menyajikan pengembangan ragam ekspresi Budaya Panji tersebut dalam kegiatan wisata. Rumusan masalah dalam penelitian ini adalah bagaimana model wisata Budaya Panji? Metode penelitian yang digunakan adalah kualitatif deskriptif sumber data primer diperoleh melalui wawancara dan eksperimen perjalanan wisata bertema Panji yang diselenggarakan oleh Lab of Tourism, data sekunder melalui studi literatur terkait. Kesimpulan penelitian ini adalah, model wisata Budaya Panji dapat diterapkan dalam tiga kegiatan wisata, pertama, memadukan ekspresi Budaya Panji dalam seni pertunjukan topeng dengan artefak. Kedua, menampilkan ekspresi Budaya Panji dalam seni pertunjukan dengan konsep Heritage Performing Art di situs atau candi. Ketiga, archaeological trail di Gunung Penanggungan, di mana gunung ini dikenal sebagai Gunung yang disucikan di masa Majapahit dengan nama Pawitra. Banyak situs dan punden berundak yang didirikan di lereng gunung, di antaranya Candi Kendallsodo yang berisi relief Cerita Panji dan Candi Selokelir tempat ditemukannya area Panji.Panji story that was growing rapidly at the time of Majapahit Empire, tells of the Kadiri kingdom. Variety of Panji cultural was expression in the form of oral literature, visual literature, performing arts and the values of life. This article reports the development of diverse expressions of Panji culture in tourism activities. The research problem is how the model of Panji Culture in tourism activities? The method used in this research is qualitative descriptive, where the source of primary data obtained through interviews and Panji thematic tour experiment held by Lab of Tourism, and secondary data through the study of related literature. The conclusion of this study are as follows, the model of PanjiCulture can be applied in three traveling activities. First, combining Panji Cultural expression in the performing arts of mask with artifacts. Second, watching Panji Cultural expression in the performing arts with the concept of Heritage Performing Art in the site or temple. Third, the archaeological trail at Mount Penanggungan, where the mountain is known as the Sanctified Mountain in Majapahit's time under the name Pawitra. Many sites and punden terraces are erected on the slopes, including Kendalisodo temple containing reliefs Story of Panji and Temple Selokelir where the discovery of Panji's statue.